Awareness Regarding Occupational Health Hazards and Risks of Zoonoses Associated with Livestock Rearing Among Male and Female Workers in Uttar Pradesh - Tripathi, Hema; Tripathi, B N; Shyam, Janmoni; Balaraju, BL (Indian Journal of Extension Education, 2016)
The present study was carried out in the state of Uttar Pradesh. Empirical data were collected personally through an  interview schedule to understand the level of awareness of 1080 families (540 women + 540 male workers) covering 54  villages with respect to occupational health hazards and risk of zoonoses in rearing their livestock. Although study  revealed significant differences in the level of awareness between male and female respondents, both had gross lack of  knowledge of various diseases associated with their work and implications of being infected with zoonotic diseases, and  other biological, chemical, physical and psychological health hazards posing serious public health threats. The reason  may be partly due to lack of education and exposure regarding safe handling and management of their animals. The study  implies that policies and programmes should be made mandatory to be implemented with support of state department of  animal husbandry, NGOs, KVKs for raising level of awareness among the livestock owning community. Information  may be provided during training and other routine programs by keeping it in syllabus as one of the components of  package of practices. It will definitely help in reducing the health risks and other hazards in livestock farming
Keywords: Occupational health hazards; zoonoses